Technology, democracy and participated knowledge = Tecnologia, democrazia e conoscenza partecipata - Pereira, Paula Cristina (2019)
In the recognition of the semantics of innovation and the technological means of the contemporary world, this text intends to analyze some effects of the technological-political regulations (of the capitalist model) in the building of science and the growing relevance of the knowledge economy, as well as assess the challenges of new practices of knowledge production towards the democratization of knowledge. Given a «cyber-imperial» model of technological praxis that involves the desire to appropriate individuals and the world, we try to assess the possibilities of decreasing the elitism of the technological culture and of configuring an awareness of the common as a model of production of meaning and social participation in order to sustain a renewed intellectual majority: the opening of reflection, mediated by a practical wisdom, to spheres of learning and knowledge - generated by common citizens who collaborate and investigate around common interests and assets - that express the capacity of participated knowledge in innovation.